PENERAPAN PROFIL PELAJAR PANCASILA DALAM MEMBENTUK KARAKTER WIRAUSAHA SISWA DI SMA NEGERI 2 SLAWI - Fahmi, Efa Syafira; Hendaryati, Neni; Basukiyatno, Basukiyatno (Universitas Tanjungpura, 2025)
This research explores the implementation of the Pancasila Student Profile in shaping the entrepreneurial character of 11th-grade students at SMA Negeri 2 Slawi. The study aims to: (1) analyze the implementation of the Pancasila Student Profile in entrepreneurial character formation, (2) identify the core values of Pancasila contributing to this character development, and (3) examine the challenges encountered during its implementation. Data were collected from three teachers, one teacher as the P5 project coordinator, two economics teachers, and six students. This research uses a qualitative descriptive case study approach. Data collection methods included observation, interviews, and documentation. The results of this study: 1) The implementation of the Pancasila Student Profile at SMA Negeri 2 Slawi through the P5 Project on the theme of entrepreneurship has run optimally with a systematic approach and practical training from external parties, 2) Pancasila values such as creativity, mutual cooperation, independence, noble morals, and critical reasoning play an important role in shaping student entrepreneurial character, 3) Obstacles such as limited facilities, uneven participation, and fear of failure are successfully overcome through creative strategies, motivation systems, and student selfreflection. SMA Negeri 2 Slawi implements entrepreneurship-themed P5 to shape students' entrepreneurial character through experiential activities. Students are involved in the entire business process, supported by the values of creativity, mutual cooperation, independence, critical reasoning, and noble character. Although the program faced facility and participation constraints, the reflection and reward-punishment approach helped overcome them.